2018
DOI: 10.4038/jula.v21i2.7922
|View full text |Cite
|
Sign up to set email alerts
|

Top Fifty Highly Cited Publications on the Internet of Things

Abstract: The present study aimed at analyzing the publication pattern of highly cited research publications of Internet of Things. Web of Science citation database was used to extract data for the study. The top fifty highly cited publications were considered as the sample of this study. The data were analyzed based on publication year, document type, source title, time cited, usage count, authorship pattern, collaborative coefficient, research collaboration, and research areas. The findings revealed that majority of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… Quantitative Selection : The articles were also selected according to data parameters; number of citations and journal’s impact factor, which meant eliminating articles prior to 2017 without citations and articles published in journals with no impact factor. These criteria were defined so as to select articles with a strong relation between the variables studied (Jayasekara & Abu, 2018 ) and with a strong scientific basis, as well as aiming to establish precise classification criteria (Acedo et al, 2006 ) representative of the population. Concluding this stage left 94 articles.…”
Section: Dt-ac Framework—construction Methodologymentioning
confidence: 99%
“… Quantitative Selection : The articles were also selected according to data parameters; number of citations and journal’s impact factor, which meant eliminating articles prior to 2017 without citations and articles published in journals with no impact factor. These criteria were defined so as to select articles with a strong relation between the variables studied (Jayasekara & Abu, 2018 ) and with a strong scientific basis, as well as aiming to establish precise classification criteria (Acedo et al, 2006 ) representative of the population. Concluding this stage left 94 articles.…”
Section: Dt-ac Framework—construction Methodologymentioning
confidence: 99%
“…Citation and altmetric analysis of research data repositories exhibited disciplinary differences in the obtainability and extent of altmetrics scores (Peters, Kraker, Lex, Gumpenberger, & Gorraiz, 2016). The highly cited publications in the Internet of Things (IoT) revealed that computer science and telecommunication were the prominent research topics (Jayasekara & Abu, 2018). Comparative analysis of the relationship between the citations and online attention in medical literature highlighted weak correlations and diverse predictors which may affect editorial decisions (Chapa, Haq, & Cifu, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%